A data-driven model of macrophage polarization states reveals an IFN macrophage signature in active Crohn’s disease - Lowe, Sarina C.; Leitman, Madelaine; Yan, Noah; Hoffmann, Alexander (Frontiers in Immunology, 2025)
Macrophages are key innate immune cells responsible for initiating and coordinating immune responses. A major determinant of macrophage function is their tissue-context-dependent polarization state, regulated by the cytokines present in the tissue microenvironment. Yet, the capability of characterizing macrophage polarization states in clinical studies remains limited. Here, we used a defined set of cytokines to polarize human PBMC-derived macrophages and determine their transcriptional signatures and stimulus responsiveness. The resultant atlas of transcriptional signatures for human macrophage polarization states was applied to a dataset of intestinal biopsies from Crohn’s disease patients and healthy controls. Our analysis identified a dominant population of IFNγ-polarized macrophages in areas of active Crohn’s intestinal inflammation and a loss of wound healing IL-4-, IL-10- and IL-13-polarized macrophages. This study demonstrates that in vitro datasets of macrophages in defined conditions can be leveraged to interpret the functionality of cells transcriptional profiled in clinical studies.